The role of prior information on consumer acceptance of insect-based food and feed in Europe: evidence from a discrete choice experiment - Mariam Nikravech; Emilia Cubero Dudinskaya; Birgit Anika Rumpold; Ana Isabel de Almeida Costa; Raffaele Zanoli; Nina Langen (Future Foods)
Insects are a promising alternative source of protein and micronutrients. Their inclusion in human diets and as feed for animals destined for human consumption has been endorsed by the European Commission to promote the achievement of the Sustainable Development Goals (SDGs) of food security (SDG 2) and responsible production and consumption (SDG 12). However, in Germany, Italy and Portugal, their use as food is hampered by low consumer acceptance and unfamiliarity with insects as part of a regular diet. Previous research has demonstrated that modifying the choice architecture, such as providing additional information on positive insect consumption outcomes, affects consumers' choices. In this study, we analyze the effect of information on consumer preferences for insect-based and insect-fed chicken meatball alternatives in three European countries: Germany (N = 516), Italy (N = 502) and Portugal (N = 250). In particular, we inspect whether different information scenarios affect consumer preferences for insect-based food products as a more sustainable alternative to meat products using a discrete choice experiment (DCE) embedded in an experimental design. Results indicate that providing prior information about the sustainability of meat alternatives increases the acceptance of insect-based meat alternatives in Germany and Italy. However, there is no evidence that making the insect-protein content more salient is associated with an increased preference for insect-based meatballs.